EDUCATION FINANCING MANAGEMENT IN THE ERA OF MERDEKA BELAJAR - Wahyuni, Tri (Jurnal Administrasi Pendidikan, 2024)
The purpose of this paper is to explain the description related to how education financing management is carried out in the era of independent learning. The research method used in making this paper is descriptive qualitative which uses document studies as data collection. Education financing is very necessary for school programs, namely financing the eight National Education Standards, to support the achievement of the school's vision and mission and create quality human resources. With the inauguration of the launch of the independent curriculum by the Ministry of Education, Culture, Research, and Technology (Kemendikbudristek) as an effort to overcome the learning crisis (Learning Loss), education financing also affects the success of education programs. While one of the education programs is the Independent Learning Program. So that it affects the funds distributed by the central government to schools, namely BOS (School Operational Assistance) funds, both from the distribution system, utilization, and accountability. With the current education financing system in the Independent Learning Era, it is hoped that it will be able to support, guarantee the development of the quality and quality of education and the implementation of the Independent Learning program.